EMOTIVE-EXPRESSIVE POTENTIAL OF PHRASEOLOGY OF LINGUISTIC IDENTITY: VLADIMIR PUTIN - Sedykh, Arkadiy; Buzinova, Lyudmila; Pashkovskaia, Natalia; Chechetka, Valentina; Sidorova, Tatyana (Revista Inclusiones, 2020)
The article deals with the linguistic identity of the politician on the material of statements of V.V. Putin. The politician's discourse is studied based on the interpretative analysis of phraseology. The linguistic consideration of systemic emotive means is carried out in light of the anthropocentric concept. Being an integral part of intellectual culture, emotions, although universal, are verbalized in specific ways in different languages due to speakers' subjective interpretation of the world around them which is undoubtedly of interest to linguistics. The linguistic-psychological and purely linguistic interpretation of data presented in language makes it possible to view the latter as the representation of special knowledge behind the facts of the natural language and as the representation of constructs of the emotive-expressive potential. The studied linguistic identity utilizes particular strategies and tactics of verbal influence on the audience that include a special psychosomatic component.